Battling Siki : a tale of ring fixes, race, and murder in the 1920s - Benson, Peter, 1932- (University of Arkansas Press, 2006)
"Battling Siki was once one of the four or five most recognizable black men in the world and was written about in detail by such figures as Ring Lardner and his son John, Damon Runyon, and Westbrook Pelger. One can find his legacy in the name of a popular rock group, one of Che Guevara's lieutenants, a character on Xena, Warrior Princess, and the Battling Siki Hotel in the fighter's homeland, Senegal. Peter Benson's biography - the first ever of this controversial and misunderstood boxer, the first African to win a world championship - delves into the complex world of sports, race, colonialism, and the cult of personality in the early twentieth century." "Born Amadou Fall, Siki was taken from Senegal to France by an actress and assumed the name Louis M'barick Fall. After an inauspicious beginning as a boxer, he served in World War I with distinction then returned to boxing and complied a most impressive record (forty-three wins in forty-six bouts). Then, on September 24, 1922, at Paris's Buffalo Velodrome, before forty thousand stunned spectators (including a young Ernest Hemingway, who wrote about the fight). Battling Siki, employing his trademark "windmill" punch, fought and defeated the reigning world and European light-heavyweight champion, Georges Carpentier." "The colorful Siki spent a fortune partying and carousing, was arrested for firing pistols in the air, and was frequently seen on the streets of Paris, dressed in flashy clothes, walking his pet lion cubs on a leash. But he also provoked scandals by exposing the corruption of the fight game in France, speaking out boldly against racism, and being arrested for deliberately defying the code of racial segregation in the American South. Newsmen largely created Siki's flamboyant image. In fact, the real Siki, while he certainly did like to party, was also an intelligent and socially conscious person, who detested the media's image of him as a simple-minded drunken savage."--BOOK JACKET.